Empirical aesthetics of bridges - Mei Yang; Claudia Damiano; Paul Gauvreau; Dirk B. Walther (PLoS ONE, 2025)
Bridges are works of public infrastructure designed to perform a practical function. They are unique among works of engineering in that they also have a significant aesthetic dimension. At their best, they inspire awe and wonder. At their worst, they are eyesores. Little is known about what shapes the aesthetic appeal of bridges. Here we explore how visible features originating primarily from practical considerations relate to aesthetic judgements of bridges. Our dataset comprises of images of 318 bridges from around the world, rated by 254 participants for aesthetic pleasure, interest, complexity, and safety. Civil engineers annotated each bridge’s type, depth, visible material, age, and aesthetic premium. Using Factorial Analysis of Mixed Data, we found two significant dimensions. The first dimension, “aesthetics”, shows strong correlations among aesthetic, complexity, and interest ratings and is related to bridge type. The second dimension, “perceived safety”, relates subjective ratings of safety to bridge age and material. Analyses of visual features, using the Mid-Level Vision Toolbox, shows that contour length and angularity are predictors of the “aesthetics” dimension. For example, cable-stayed bridges are represented by many short and angular contours and are generally rated as more complex, interesting, and aesthetically pleasing. Conversely, slab bridges are often represented by a few long contours and are rated as uninteresting and not aesthetically pleasing. Our study offers the first systematic attempt to collect and analyze subjective ratings of bridge aesthetics, paving the way for empirically supported decisions for the design of bridges and, potentially, other works of public infrastructure.